"Never Battle Alone": Egirls and the Gender(ed) War on Video Game Live Streaming as "Real" Work. (July 2022) - Tran, Christine H.
From 2018 to 2021, the "egirl" witnessed a radical shift from her origins as a sexualized slur in online gaming. Through critical discourse analysis of news media of this period, this paper interprets this transformation within two primary phenomena: (1) the growth of women game influencers who reclaimed "egirl" slurs in their self-branding and (2) the launch of "Egirl.gg, " a platform for paid gaming companions. I argue that live streaming platform Twitch.tv, and the expansive ecosystems of labor its demand from streamers, were integral to this re-authorization of who can play as themselves in a patriarchal gaming culture. Here, I extend Ergin Bulut's framework of "ludic authorship" to delineate how stakeholders in game streaming industries masculinize the cultural labor of "authenticity." The ambivalent embrace of "egirling" via streaming cultural logics further complicates the work of women gamers who must work harder to realize careers in platformed entertainment.